EVALUATING OF POLICE GOES TO SCHOOL PROGRAM IN IMPROVING TRAFFIC SAFETY IN WEST JAVA - Dewi Maulina; Guritnaningsih Guritnaningsih; Dewa Fajar Bintamur (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2020)
This study aims to describe of the implementation of the Police Goes To School (PGTS) education program and evaluate the effectiveness of the PGTS education program to improve traffic safety among junior and senior high school students, particularly in West Java. The study was conducted using mixed design in schools that received the PGTS program and those who did not get the PGTS program. Interviews were conducted with 4 teachers and 8 police officers. We distributed questionnaires to 202 junior high school students and 173 senior high school students in Bogor and Cirebon, which measured knowledge, attitudes and behaviors related to traffic safety. The results showed that the implementation of the PGTS program to junior high school students is effective in increasing students' knowledge about traffic rules and attitudes towards traffic order. For high school students, the PGTS program is effective in increasing the frequency of safe riding behavior. In the implementation of the PGTS program, there are still limitations in the variety of delivery methods by the police. They use mostly the lecture and simulation methods. On the school side, the efforts made tend to be mainly in the form of appeals. Other approaches such as incorporating curricular learning have not been touched to teach traffic safety to students. Penelitian ini bertujuan untuk melihat gambaran pelaksanaan program edukasi Police Goes To School (PGTS) dan mengevaluasi efektivitas program edukasi PGTS untuk meningkatkan keselamatan berlalu lintas di kalangan siswa SMP dan SMA, khususnya di Jawa Barat. Penelitian dilakukan menggunakan mixed design pada sekolah yang mendapatkan program PGTS dan yang tidak mendapatkan program PGTS. Wawancara dilakukan terhadap 4 orang guru dan 8 orang petugas kepolisian. Penyebaran kuesioner dilakukan pada 202 siswa SMP dan 173 siswa SMA di Bogor dan Cirebon, yang mengukur pengetahuan, sikap dan perilaku yang berhubungan dengan ketertiban lalu lintas. Hasil penelitian menunjukkan bahwa pemberian program PGTS pada siswa SMP menunjukkan efektivitas dalam meningkatkan pengetahuan siswa tentang peraturan lalu lintas dan sikap terhadap ketertiban berlalu lintas. Pada siswa SMA, program PGTS efektif dalam meningkatkan frekuensi perilaku mengendarai sepeda motor secara aman. Dalam pelaksanaan program PGTS, masih terdapat keterbatasan dalam variasi metode penyampaian program yang dilakukan polisi. Pelaksanaan program lebih banyak hanya menggunakan metode ceramah dan simulasi. Di pihak sekolah upaya yang dilakukan juga cenderung hanya berupa himbauan. Pendekatan lain seperti memasukkan dalam pembelajaran kurikuler belum tersentuh untuk mengajarkan keselamatan berlalu lintas pada siswa.